Significance of Assessment in Learning: The Role of Educational Assessment Tools - Zhou, Ming (Science Insights Education Frontiers, 2023)
It has been widely acknowledged that assessment is an integral part of any effective educational system. It involves a wide variety of methods or tools that educators use to evaluate, measure, and document the academic readiness, learning progress, skill acquisition, and academic results of students. In his Dictionary of Education Evaluation, Tao (1998) defines educational assessment as a process in which educators make objective evaluation of educational activities, processes, and outcomes through systematic information collection and analysis by using practical, scientific methods, with the purpose of supporting students’ continuous improvement and providing evidence for educational decision-making.